ANALYSIS OF ROAD PERFORMANCE AND EQUIPMENT ON THE LETDA ABDUL ROZAK SECTION, PALEMBANG - Wahab, Wahyuni; Eka Putri, Eprilia; Rosyad, Farlin; Irham, Irham (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In an effort to improve services for existing traffic, one of the efforts made is to improve the quality of road equipment. As explained in Law Number 22 of 2009 concerning Traffic and Road Transportation Article 25, it states that every road used for traffic must be equipped with road equipment in the form of one of which is traffic signs. The Palembang City Government, especially the Palembang City Transportation Agency itself, does not yet have data on road equipment, such as traffic signs that have complete attribute data. However, the existing condition of incomplete road equipment causes the management of road equipment data to not be managed properly. Which will have an impact on the obstruction of every activity such as monitoring and maintenance of existing Road Equipment. So that it will have an impact on decision making to improve road services and safety. In addition to the incomplete Road Equipment data, the condition of the signs on Jalan Letda Abdul Rozak is also absent. In addition to the problems with road equipment signs, according to data obtained from the author's analysis results, it is known that the free flow speed of light vehicles is 44.7 (km/hour) while the function of the collector road with the results of the analysis in the field, the maximum speed must be below 30 (km/hour) this causes Jalan Letda Abd Rozak to often experience congestion, especially during work and school hours. Keywords: services for existing traffic, quality of road equipment, congestion,